Integrating an electrically active colloidal quantum dot photodiode with a graphene phototransistor - Ivan Nikitskiy (Nature Portfolio, 2016)
The combination of fast photo-response and high gain plays a pivotal role in photodetector devices. Here the authors combine a colloidal quantum dot photodiode with a graphene phototransistor to overcome the speed, quantum efficiency and linear dynamic range limitations of available phototransistors.